In operando study of lithium batteries by coupling X-ray photoelectron spectroscopy and impedance spectroscopy - Morales Ugarte, Jorge Eduardo (2019)
Descargue el texto completo en el repositorio institucional de la Communauté Université Grenoble Alpes: https://tel.archives-ouvertes.fr/tel-02506388